High-density brittle material structure with infiltration
By using low-pressure transfer technology to manufacture high-density oxide ceramic structures in flexible equipment and oxide all-solid lithium-ion secondary batteries, the performance deterioration caused by residual stress is solved and high-performance ceramic materials are achieved.
Patent Information
- Application Number
- CN202080039682.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-05-29
- Filing Date
- 2020-05-27
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2040-05-27
AI Technical Summary
The existing manufacturing methods of oxide ceramics have residual stress problems in flexible equipment and oxide all-solid lithium-ion secondary batteries, resulting in deterioration of piezoelectricity, dielectricity and ion conductivity.
By repeatedly transferring the thin layer of brittle material particles to the substrate at a lower pressure than the broken particles, a high density aggregate is formed, ensuring a void ratio of less than 20%, and forming grid-shaped nano-voids between the particles.
The manufacturing of high-density oxide ceramic structures is achieved, reducing internal stress, improving piezoelectricity, dielectricity and ion conductivity, and reducing the need for sintering treatment.
Smart Images

Figure CN113950764B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a new structure of oxide ceramics.
[0002] Oxide ceramics are widely used as electronic ceramics that utilize piezoelectricity, dielectric properties, etc. Recently, in order to adapt to wearable devices, there is a demand for the development of "flexible devices" that combine soft organic materials such as plastics with electronic ceramics.
[0003] In addition, regarding the "oxide all-solid-state lithium-ion secondary battery" that has attracted attention as the next generation of storage batteries, it is required to prepare a positive electrode composite material and a negative electrode composite material in which the active material of oxide ceramics, a solid electrolyte, an auxiliary agent for supplementing conductivity, etc. are uniformly and seamlessly deposited on a metal foil, and then these positive electrode composite materials and negative electrode composite materials are seamlessly joined using an oxide solid electrolyte, which is a very advanced technology. Background Art
[0004] Generally speaking, oxide ceramics require very high sintering temperatures for high-density sintering. However, cheap and flexible metal foils such as plastics, aluminum, and copper used in flexible devices and oxide all-solid-state lithium-ion secondary batteries have very low heat resistance and cannot withstand the sintering temperature and oxidative atmosphere of oxide ceramics.
[0005] Therefore, in the past, when making oxide ceramic structures, methods such as lowering the sintering temperature or imparting reduction resistance by adding additives, depositing oxide ceramic films at a temperature lower than the sintering temperature by applying sputtering, PLD, CVD, MOD (sol-gel method), hydrothermal synthesis, screen printing, EPD, Cold Sintering, etc., adjusting the shape of raw material particles to nano-sized sheets or cubes and stacking them, and aerosol deposition (AD) methods in which raw material particles are solidified by colliding with a substrate at room temperature are used.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2016-100069
[0009] Patent Document 2: Japanese Patent Application Publication No. 2006-043993
[0010] Patent Document 3: Japanese Patent Application Publication No. 2012-240884
[0011] Patent Document 4: Japanese Patent Application Publication No. 2012-188335
[0012] Patent Document 5: Japanese Patent Application No. 2018-110527
[0013] Non-patent literature
[0014] Non-patent document 1: Yoshio Uchida et al., Sumitomo Chemical 2000-I, p.45 Summary of the invention
[0015] Problem that the invention aims to solve
[0016] As is known, oxide ceramics have a high Young's modulus as a whole and a very high hardness, and therefore are easily affected by residual stress acting inside.
[0017] However, it is known that in the manufacturing methods that are accompanied by heat treatment, such as sputtering, PLD, CVD, MOD (sol-gel method), hydrothermal synthesis, screen printing, EPD, and Cold Sintering, which have been used in the past, residual stress will be generated in the oxide ceramic film due to the slight difference in linear expansion coefficient between the substrate and the oxide ceramic film, even if the deposition is performed at a temperature lower than the sintering temperature, resulting in degradation of the piezoelectric and dielectric properties.
[0018] Furthermore, even in the case of a ceramic film deposited at room temperature by the AD method or the like, there is a problem that the internal compressive stress caused by the shot peening effect becomes a residual stress, which causes deterioration of the dielectric properties.
[0019] In oxide all-solid-state lithium-ion secondary batteries, there is a problem that cracks are generated in the active material itself due to changes in internal stress caused by expansion and contraction caused by insertion and extraction of lithium ions in the active material, resulting in performance degradation.
[0020] It is known that the polarization mechanism of ferroelectrics showing large piezoelectricity comes from the fact that the domain wall formed by the anisotropy of the crystal moves by applying a high electric field, achieving polarization reversal and polarization rotation. However, if there is a part where a clean interface is not formed, a part where the crystallinity is incomplete (a part where the lattice image observed by TEM is unclear), or a part containing oxygen defects, the movement of the domain wall is pinned or clamped there, and sufficient polarization reversal and polarization rotation cannot be achieved, resulting in degradation of ferroelectricity and piezoelectricity. Therefore, it is necessary to synthesize oxides with high crystallinity and few defects.
[0021] Similarly, in oxide solid electrolytes, lithium ions mainly move along the conduction paths formed in the crystals. Therefore, if there are incompletely crystalline parts between the particles or binding materials that do not show ion conductivity of lithium ions, the ion conductivity will be reduced, so high-quality crystals are required.
[0022] However, if low-temperature deposition is performed using conventional techniques such as sputtering, PLD, CVD, MOD (sol-gel), hydrothermal synthesis, screen printing, EPD, and Cold Sintering to promote crystal growth and obtain a highly dense film, it is very difficult to obtain high crystallinity and the applicable substrates are also greatly limited.
[0023] In addition, the AD method can utilize high-quality oxide ceramic raw material particles to deposit a film, but the miniaturization of the raw material particles unique to the AD method exhibits a size effect that reduces piezoelectricity and dielectric properties. There are also problems in the oxide solid electrolyte, such as the formation of a large number of grain boundaries that serve as barriers to the movement of lithium ions and reduced ion conductivity.
[0024] Furthermore, in methods of depositing a ceramic film in an aqueous solution such as a hydrothermal synthesis method and an EPD method, it is known that residual hydroxyl groups at the grain boundaries may increase the leakage current of the ferroelectric and hinder the conduction of lithium ions.
[0025] Ceramic deposition techniques such as sputtering, PLD, CVD, MOD (sol-gel), hydrothermal synthesis, screen printing, and EPD as prior art are techniques for depositing oxide ceramic films on substrates. However, in oxide all-solid-state lithium-ion secondary batteries, etc., it is necessary to form a highly dense ceramic film between aluminum foil and copper foil as current collectors, and a new deposition method that can achieve a different bonding from the previous ceramic deposition techniques is required.
[0026] In the AD method, deposited sulfide solid electrolytes are placed opposite each other and further pressurized to achieve bonding accompanied by high densification of the sulfide solid electrolyte layer (Patent Document 1). However, when applied to oxide solid electrolytes in which lithium ions move within crystals, a large number of grain boundaries that serve as barriers to the movement of lithium ions are formed as the process becomes smaller, so bonding without breaking up the raw material particles becomes a problem.
[0027] Furthermore, a method that can achieve high-density deposition at atmospheric pressure, as compared with vacuum processes and reduced-pressure processes such as sputtering, PLD, CVD, and AD, is desired.
[0028] Unlike conventional deposition methods such as sputtering, PLD, CVD, MOD (sol-gel), hydrothermal synthesis, screen printing, and EPD, in which crystal growth is performed by heat treatment, in a press forming method in which raw material particles are loaded into a mold and press formed to obtain a structure, as shown in non-patent document 1, it is a problem to make the relative density of the structure greater than 80% (the void ratio less than 20%) without crushing the raw material particles.
[0029] It is known that, generally speaking, no matter what kind of oxide ceramic particles are, they must have "cohesive bonding force". If the particles become smaller and the specific surface area becomes larger, the bonding force acts more strongly, so it is easy to cohere. In the previous press forming method, the cohesive bonding force acts before the particles completely fill the voids, and a strong friction force caused by the forming pressure is also applied to them, so it is impossible to produce highly dense structures. In order to produce a structure with a relative density of more than 80% (porosity of less than 20%) by press forming, a method accompanied by crushing of raw material particles is adopted in the same way as the AD method (Patent Document 2).
[0030] In addition, the Cold Sintering method is a method for producing high-density oxide ceramics by providing an amorphous layer around raw material particles and applying pressure. However, in non-heat treatment, an amorphous layer remains around the raw material particles, which leads to problems such as reduced piezoelectricity, dielectric properties, and ion conductivity. As a result, there is also the problem of requiring heat treatment to grow only the amorphous layer into high-quality crystals. In addition, the limited number of raw material particles that can form an amorphous layer is also a problem.
[0031] Nanosheets obtained by thinly exfoliating oxides (Patent Document 3) can deposit a dense oxide layer without heat treatment, but since oxide sheets with a thickness of several nanometers are deposited one layer at a time, there is a problem of depositing to a thickness of submicron level.
[0032] Similarly, recently, a technique for regularly arranging cubic nanoparticles three-dimensionally has attracted attention (Patent Document 4). However, in reality, cracks are generated over a wide range due to extremely small size differences in the cubic raw material particles, and there is a problem in providing a uniform film without gaps on a substrate.
[0033] Compressed powders with a porosity higher than 20%, and molded bodies in which more than 20% of the voids are filled with resin and particles are bonded with a binder, also have the problem of not being able to obtain the functionality caused by the crystal structure. For example, in the case of piezoelectrics and ferroelectrics, the relative dielectric constant of the functional oxide is 50 to 1000 times higher than that of the resin, so the electric field concentration occurs in the resin with a low relative dielectric constant, resulting in problems such as failure to apply a sufficient electric field to the oxide, increased leakage current, and reduced dielectric breakdown strength. In oxide all-solid-state lithium-ion batteries, even if a polymer electrolyte can be mixed or impregnated in the voids of the oxide solid electrolyte, the Li ion conductivity of the polymer electrolyte is 50 to 1000 times lower than that of the oxide solid electrolyte, which limits the ion conductivity of the polymer electrolyte and does not produce the diffusion of Li ions required for charging and discharging.
[0034] Means used to solve problems
[0035] The inventors of the present invention have conducted intensive research on a structure that can solve the above-mentioned problems of the prior art, and found that by repeatedly transferring a thin layer of brittle material particles such as PZT on a transfer plate to a substrate at a pressure lower than that of crushing the particles, a structure in which the particles are densely arranged and the porosity is less than 20% can be made, and a prior application (Patent Document 5, which was not yet published at the time of the present invention's application) was filed. The inventors of the present invention further found that the structure has grid-like fine nano-voids between the densely arranged particles that extend over the entire structure, and found that the structure can solve the above-mentioned problems. Liquid organic matter such as resin and silicone oil can also be impregnated in the nano-voids, and the liquid resin can also be solidified after being impregnated in a high-density agglomerate.
[0036] Specifically, the second particles smaller than the first particles are filled in the gaps still existing between the densely arranged first particles with a larger particle size, thereby producing an extremely dense aggregate structure with a void ratio of 20% or less.
[0037] The high-density agglomerate of the present invention maintains functionality due to the crystal structure because the raw material particles are almost not broken by the above-mentioned preparation method. In addition, by suppressing crystal growth and the breakage of raw material particles as much as possible, it has a grid-like structure in which almost all gaps are connected. The high-density agglomerate of the present invention can be regarded as a structure in which the space existing in the powder mixed with the first particle and the second particle is reduced to a structure in which the distance between particles becomes a nanometer region, and therefore also has the characteristic that the specific surface area of the powder is roughly the same as the specific surface area of the high-density agglomerate of the present invention.
[0038] like Figure 1 As shown in (a), the void structure of the high-density agglomerate preferably has a feature that the voids between the first particles have nanovoids formed by the second particles.
[0039] In contrast, in a conventional sintered body that is subjected to heat treatment, nano-voids disappear due to crystal growth, and high densification due to crushing of raw material particles also destroys nano-voids in the same manner. Figure 1 As shown in (b), as a result, a structure in which voids including triple points at grain boundaries are dispersed is formed.
[0040] The following is an example of making a high-density agglomerate.
[0041] As a transfer plate, a metal plate with an elastic modulus high enough to prevent any brittle material from remaining during pressure transfer is used. When attaching particles made of brittle material to the transfer plate, firstly attach the first particles having a large particle size, and then attach the second particles having a particle size smaller than the first particles thereon. A substrate made of metal or carbon having an elastic modulus low enough to allow the brittle material to attach during pressure transfer is arranged on the surface to which the second particles are attached. By applying pressure lower than that required to crush the particles, the thin layer of brittle material attached to the transfer plate is transferred to the substrate. Next, the first and second particles are attached to the transfer plate by the same method. The thin layer side of the brittle material of the substrate to which the thin layer of brittle material is transferred is arranged on the surface to which the second particles are attached. By applying pressure, the thin layer of brittle material attached to the transfer plate is transferred onto the thin layer on the substrate. By repeating the stacking process, a structure of brittle material having a desired thickness is produced on the substrate.
[0042] When forming a thin layer of brittle material on the above-mentioned transfer plate, the first particles with a large particle size can be attached first, and then a mixture of the first particles and second particles with a particle size smaller than the first particles are attached thereon, and then the second particles are attached thereon.
[0043] Furthermore, when a thin layer of a brittle material attached to a transfer plate is transferred to a base material under pressure, vibration may be applied in the lateral direction.
[0044] Specifically, the present application provides the following inventions.
[0045] 〈1〉 A high-density agglomerate, characterized in that it is a high-density agglomerate of brittle material particles, and there are interfaces between particles that are bonded to each other and non-bonded voids between the brittle material particles constituting the high-density agglomerate, the volume ratio of the voids to the overall volume of the high-density agglomerate, that is, the void ratio, is less than 20%, and the volume of the voids connected to the apparent outer surface of the high-density agglomerate is greater than 65% relative to the overall void volume of the high-density agglomerate.
[0046] 〈2〉 The high-density agglomerate according to 〈1〉 is characterized in that the brittle material particles constituting the high-density agglomerate are composed of first brittle particles and second brittle particles smaller than the first brittle particles, the second particles are present in the gaps between the mutually bonded first particles, and there are bonding interfaces between the multiple second particles in the gaps and between the second particles and the surrounding first particles and non-bonded gaps.
[0047] <3> The high-density agglomerate according to <2>, characterized in that the particle size of the second particles is less than 1 μm.
[0048] <4> The high-density agglomerate according to <1>, characterized in that the average gap width between the brittle material particles is less than 200 nm.
[0049] <5> The high-density aggregate according to any one of <1> to <4>, wherein silicone oil, a liquid in which nanoparticles having a particle size of 100 nm or less are dispersed, or a liquid resin is impregnated in voids in the high-density aggregate.
[0050] <6> The high-density aggregate according to <5>, wherein the liquid resin impregnated into the high-density aggregate is solidified.
[0051] <7> An electrical component unit, characterized in that it is formed by stacking a film composed of a high-density aggregate described in any one of <1> to <4>, an electrode layer, and a conductive mesh-shaped foil in sequence on both sides of a substrate, wherein the high-density aggregate is impregnated with a resin.
[0052] <8> An electrical component unit, which is formed by stacking a plurality of units described in <7>.
[0053] <9> A solid battery comprising a first polymer impregnated in the high-density aggregate according to any one of <1> to <4>, wherein the first polymer has ion conductivity.
[0054] <10> The solid state battery according to <9>, wherein
[0055] The solid battery has:
[0056] the first polymer; and
[0057] a second polymer formed on top of the first polymer,
[0058] The second polymer has ion conductivity,
[0059] The second polymer contains particles of brittle material.
[0060] <11> The solid battery according to <10>, wherein the solid battery is in a bent shape.
[0061] <12> The solid battery according to <10> or <11>, wherein the solid battery is in a bent and stacked shape.
[0062] Effects of the Invention
[0063] According to the present invention, a powder of raw material particles of a brittle material having high crystallinity is pressurized at a pressure lower than that required for crushing the particles and is thinly press-formed to form a structure in which the raw material particles are densely arranged, and then a structure in which the raw material particles are similarly densely arranged is stacked on the structure in an integrated manner by press-forming, thereby obtaining a high-density agglomerate having a relative density of more than 80% (a void fraction of less than 20%) formed by agglomeration of the raw material particles.
[0064] In addition, the liquid / solid interface free energy generated by the contact between the fine second particles and the liquid is high, and the contact angle of the liquid is low, thereby showing excellent wettability. The voids of the high-density agglomerate of the present invention are almost all made of fine second particles, and the void width is less than 200nm, which is extremely narrow. Therefore, the high-density agglomerate of the present invention has the characteristic of producing a very strong capillary phenomenon. That is, the gas and liquid barrier properties of conventional ceramics become higher as they become more dense, but the high-density coagulation film of the present invention has the characteristic of not showing liquid and gas barrier properties even if densification is promoted, and has a very high permeability. Therefore, the high-density agglomerate of the present invention can be infiltrated into every corner of the structure even if it is a liquid with high viscosity or a liquid with high surface tension.
[0065] The brittle material structure of the present invention is formed by agglomeration of raw material fine particles, and therefore can maintain the high crystallinity of the original raw material fine particles and also generates little internal stress.
[0066] According to the present invention, sintering treatment, crushing of raw material particles, vacuum and reduced pressure processes, etc., which are required for the conventional production of high-density oxide ceramic structures, are not required, and the generation of defects in the crystal and the occurrence of internal stress associated with these processes can be suppressed.
[0067] According to the present invention, even when a high-density aggregate is subjected to sintering treatment, there is an effect of suppressing stacking shrinkage compared to the conventional sintering method involving heat treatment.
[0068] According to the present invention, by infiltrating silicone oil, resin or nanoparticles into high-density agglomerates of piezoelectrics and ferroelectrics, the electric field intensity applied to the brittle material particles of piezoelectrics and ferroelectrics can be controlled. Specifically, by infiltrating materials with lower dielectric constants than the brittle material particles of piezoelectrics and ferroelectrics, the coercive electric field can be increased and the dielectric breakdown strength can be improved. In addition, by infiltrating nanoparticles with a relative dielectric constant larger than the brittle material particles of piezoelectrics and ferroelectrics, the electric field intensity applied to the brittle material particles of piezoelectrics and ferroelectrics can be enhanced, the coercive electric field can be reduced and the piezoelectricity can be improved. In addition, by infiltrating polymer solid electrolytes into high-density agglomerates of oxide solid electrolytes, the density of oxide solid electrolytes that lithium ions can move at high speed can be increased, the moving distance of lithium ions in the polymer solid electrolyte can be shortened, and the diffusivity of lithium ions can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0069] Figure 1 This is a schematic diagram showing the difference in the structure of voids between the high-density agglomerate of the present invention and a conventional high-density ceramic sintered body.
[0070] Figure 2 This is a three-dimensional SEM image of the high-density PZT condensed film of the present invention.
[0071] Figure 3 This is a three-dimensional SEM image of a typical PZT sintered body.
[0072] Figure 4 This graph shows the difference between ceramics that can be produced by conventional ceramic methods and ceramics that can be produced using high-density aggregates, in terms of the relationship between the porosity and the volume density of voids communicating with the outer surface relative to the total voids.
[0073] Figure 5 This is a SEM image of the fracture surface of a film in which epoxy resin or PMMA resin is impregnated in a PZT high-density cohesive film.
[0074] Figure 6 This is a comparison chart of the leakage current characteristics of PZT pressed powder film and PZT high-density condensed film.
[0075] Figure 7 This is a comparison chart of the polarization characteristics of a PZT high-density condensed film containing silicone oil and a PZT high-density condensed film containing TiO2 nanoparticles.
[0076] Figure 8 It is a schematic diagram of an element unit 1 in which a PZT high-density condensed film impregnated with PMMA, an electrode layer, and a conductive grid-shaped foil are stacked in sequence on both sides of a substrate, a photograph showing the appearance of the unit 1, and a schematic diagram of an element unit 2 in which multiple units 1 are stacked.
[0077] Fig. 9 This is a photograph showing the appearance of a PZT high-density aggregated film produced using a conductive mesh-shaped foil as a base material.
[0078] Fig.10 This is a photograph showing that an integrated element unit cannot be obtained when a conductive mesh-shaped foil is directly laminated without an electrode layer and without PMMA impregnation on the PZT high-density aggregated films provided on both surfaces of a substrate.
[0079] Fig.11 This is a schematic diagram showing a production process for swelling and peeling off only the epoxy resin of the surface layer of the PZT high-density cohesive film impregnated with the epoxy resin and crosslinked, thereby exposing the electrode layer provided on the surface of the PZT high-density cohesive film.
[0080] Fig.12 This is a SEM image comparing the surface of a high-density coacervate film of PZT that was peeled off by swelling the epoxy resin in the surface layer and the surface of a high-density coacervate film of PZT that has the epoxy resin in the surface layer.
[0081] Fig.13 This is a comparison diagram of polarization characteristics between a high-density coacervate film of PZT that is peeled off by swelling the epoxy resin on the surface layer and a high-density coacervate film of PZT that has the epoxy resin on the surface layer.
[0082] Fig.14 These are SEM images of the first LCO particle and the second LCO particle.
[0083] Fig.15 These are SEM images of the first LTO particle and the second LTO particle.
[0084] Fig.16 It is a schematic diagram showing the manufacturing steps of a solid battery in which a positive electrode sheet and a negative electrode sheet are impregnated with a polymer electrolyte, and then cross-linked after being joined using the polymer electrolyte provided on the surface layer of each sheet, and a schematic diagram of a solid battery having a sheet with a polymer solid electrolyte between the positive electrode sheet and the negative electrode sheet.
[0085] Fig.17 The chart compares the charge and discharge characteristics of a solid battery in which a positive electrode sheet and a negative electrode sheet are impregnated with a polymer electrolyte, and then cross-linked using the polymer electrolyte provided on the surface layers of each sheet, and a solid battery in which a sheet with a polymer solid electrolyte is provided between the positive electrode sheet and the negative electrode sheet.
[0086] Fig.18 Schematic diagram of a solid battery made by folding battery cells and a solid battery made by stacking battery cells in a bent shape.
[0087] Fig.19The diagram is a schematic diagram of a solid battery having a polymer electrolyte layer in which brittle material particles are embedded, a photograph of a solid battery in a bent shape, and a photograph of an LED lit by using the solid batteries in a bent and stacked shape.
[0088] Fig. 20 It is the charge and discharge characteristics of a solid battery in a bent shape.
[0089] Fig.21 This is a comparison chart of the impedance characteristics of the polymer solid electrolyte between aluminum foils before and after bending. DETAILED DESCRIPTION
[0090] Example
[0091] <Example 1> Void structure of a high-density aggregated film using PZT particles
[0092] Next, a specific method for producing the structure of the present invention will be described.
[0093] PZT particles (average particle size: 1550 nm) serving as first particles adhere to the surface of stainless steel SUS304 (film thickness: 20 μm).
[0094] The first PZT particles were synthesized by the molten salt method using PZT-LQ powder made by Sakai Chemical Industry. The first PZT particles were weighed using a microanalytical balance (SHIMADZU, model: AEM-5200), moved to a 50cc glass container filled with ethanol, and dispersed for 1 minute using an ultrasonic homogenizer (SONIC & MATERIALS, model: VCX750) with 350W, 20kHz ultrasound. The solution was moved to an air brush coating system (GSI Creos, PS311 air brush kit) and sprayed on the SUS304 of the transfer plate prepared in advance on a hot plate set at 60°C, thereby attaching the first PZT particles to the SUS304 surface.
[0095] Next, the second particles are attached to the first particles so that the mixing ratio of the second particles (volume occupied by the second particles / total volume of the first particles and the second particles) is between 15% and 30%.
[0096] The spraying of the second particles is the same as that of the first particles. The second particles use PZT particles (average particle shape: 150nm). The second PZT particles are first made into a sintered body using PZT-LQ powder produced by Sakai Chemical Industry. After being made into powder using a mortar, they are placed in a zirconia ball mill tank together with zirconia balls and acetone, and crushed using a planetary ball mill. The acetone is dried, and the obtained powder is dispersed in ethanol, placed in a centrifuge, and subjected to classification treatment to obtain the second PZT particles. The second PZT particles are also dispersed in ethanol like the first PZT, and then sprayed onto the surface of SUS304 with PZT particles attached, thereby attaching to the first PZT particles.
[0097] The SUS304 with the first and second particles attached is removed from the hot plate and cut into multiple pieces of 1 cm 2 The first and second particles were pressed on a substrate of aluminum foil (film thickness 20 μm) in the shape of a disk of φ, and pressure-transferred and solidified on the substrate.
[0098] The substrate is preferably a metal or carbon with an elastic modulus below 180 GPa. It is preferably characterized by a solidification pressure that is lower than the pressure of crushing the raw material particles and is below 2 GPa. In this experiment, pressurization was performed in two ways: 1000 MPa and 400 MPa. The first and second particles were pressurized and transferred from SUS304 to an aluminum foil substrate, and this was repeated 9 times, thereby laminating a high-density condensed film of PZT (pressurized at 1000 MPa) and a pressed powder film (pressurized at 400 MPa) on the aluminum foil.
[0099] As a comparative reference example, PZT-LQ powder manufactured by Sakai Chemical Industry Co., Ltd. was sintered so that the relative density became about 80%, thereby obtaining a sintered body.
[0100] The specific surface areas of the obtained high-density coacervate films, pressed powder films, and low-density sintered bodies were evaluated by a multipoint BET method (Kr gas adsorption method).
[0101] As the true density of PZT, 8.0 g / cm 3 The specific surface area in the powder state is calculated by approximating a sphere with the average particle shape of the first and second PZT particles as the diameter. The particle size in the sintered body is the average particle size of the particles bonded to each other observed after sintering, and the specific surface area in the powder state is calculated by assuming that it exists directly as a powder. In either case, it is assumed that the PZT particles themselves are non-porous.
[0102] The weight of the PZT layer of the high-density coagulation film and the pressed powder film is obtained by measuring the weight before and after the first and second PZT particles are deposited on the aluminum foil, and the difference is obtained. The film thickness of the high-density coagulation film and the pressed powder film is obtained by observing the cross-sectional SEM image and finding the average film thickness. Based on these results, the density of the PZT layer of the high-density coagulation film and the pressed powder film is calculated, and it is divided by the true density of PZT to calculate the relative density (%) of the PZT layer, and subtracted from 100 to calculate the overall porosity (%) of the PZT layer.
[0103] The specific surface area of the PZT layer based on the BET method is evaluated in a state where the PZT film is deposited on the aluminum foil. The specific surface area of the aluminum foil is so small as to be negligible compared to the specific surface area of the PZT layer, so the specific surface area per unit weight of the entire PZT film containing the aluminum foil obtained by the BET method is converted into a value per unit weight of the PZT layer contained in the PZT film, and the specific surface area of only the PZT layer is calculated from the weight of the deposited PZT film.
[0104] The surface area measured by the BET method is the surface area from the apparent outer surface of the sample to be measured to the range that Kr as the measuring gas can reach. Therefore, the specific surface area of the PZT layer based on the BET method is equivalent to the specific surface area of the powder minus the specific surface area of the interface generated by the mutual bonding of powders when the PZT layer is formed by powders and the specific surface area corresponding to the void portion that becomes the enclosed space inside the PZT layer.
[0105] Here, the shapes of the voids in the high-density condensed film, the pressed powder film, and the low-density sintered body are uniform as a whole, so the ratio of the specific surface area of the PZT layer based on the BET method to the specific surface area of the powder can be approximated to the proportion of the voids in the overall voids of the PZT layer that are connected to the apparent outer surface of the PZT layer.
[0106] Table 1
[0107]
[0108] ※1 For each, the thickness is very thin and the void shape is uniform, so the ratio of (16) to (6) is regarded as the ratio of "the volume of the void connected to the outer surface" to "the total void volume"
[0109] The porosity of the PZT film obtained by pressing at 400 MPa is 33.5%, which is equivalent to that of a normal powder compact, but the porosity of the PZT film pressed at 1000 MPa is 10%, which is highly densified. It is shown that the specific surface area of the PZT layer of the PZT powder film and the PZT high-density condensed film is 1.29 m 2 / g, and the volume density of voids connected to the apparent outer surface relative to all voids is also above 98%. In addition, the comparison of the specific surface area of the powder in Table 1 (6) and the specific surface area of the PZT layer in Table 1 (16) means that in the PZT high-density coacervate film, the contact area between the PZT particles and the area of the part of the particle facing the voids enclosed inside by the bonding between the particles only account for about 2% of the total specific surface area of the particles. The PZT high-density coacervate film of the present invention has the characteristic that the specific surface area is roughly the same as that of the powder even if the porosity is highly densified to 10%.
[0110] The porosity of the sintered body of the comparative example is 21.8%, and the specific surface area is 0.43 m 2 / g, and the volume density of voids communicating with the apparent outer surface relative to all voids was 42.8%.
[0111] As described above, the PZT high-density condensed film of the present invention is a high-density film with a porosity of less than 20%, which could not be achieved in the past without sintering treatment and particle crushing, and has an extremely unique feature of being able to maintain a large specific surface area comparable to the specific surface area of the particles before aggregation even after aggregation.
[0112] Next, the details of the microstructure of the PZT high-density aggregated film and the PZT sintered body were investigated by three-dimensional SEM observation.
[0113] The PZT high-density coacervate film was prepared in the same manner as the sample used in the BET evaluation. The pressing pressure was 750 MPa, and the porosity of the coacervate film was 14%. As a comparative reference example, a sintered body with a porosity of 4% was prepared.
[0114] After obtaining a plane image of the surface, the surface observed by FIB is thinned (50nm thick for a high-density coagulated film and 100nm thick for a sintered body) and a plane image is obtained again. This operation is repeated, and the obtained huge image data is digitally processed to reproduce it as a three-dimensional CG, which enables numerical analysis of the fine structure, etc. The experimental conditions and results are summarized in Table 2.
[0115] exist Figure 2 (a) shows a cross-sectional SEM image of a PZT high-density condensed film used for three-dimensional SEM observation. In the three-dimensional SEM observation, the region surrounded by a quadrilateral (7 μm×7 μm) in the cross-sectional image is observed to a depth of 7 μm. Figure 2(b) shows a three-dimensional image that reproduces the fine structure of the PZT high-density condensed film, (c) shows a three-dimensional image of the void structure of the entire observed area, (d) shows a three-dimensional image of the void portion with the largest volume in the overall voids, which is interconnected and also connected to the outer surface of the observed area, and (e) shows a three-dimensional image of the isolated void portion enclosed in the interior of the observed area other than the voids connected to the outer surface. In addition, Figure 3 (a) shows a three-dimensional SEM image that reproduces the fine structure of the sintered body, and (b) shows a three-dimensional image of the void structure of the entire observed area. Figure 3 The black parts in (b) are void parts connected to the outer surface of the observed area, and the gray parts are isolated void parts inside.
[0116] from Figure 2 (a) can confirm that the PZT high-density condensed film deposited at 750 MPa is uniform and has a high density. Figure 2 (c) and (d) confirm that the void structure of the PZT high-density aggregate expands in a grid-like manner over the entire observed area, and the voids are almost completely integrated. Figure 2 (e) can confirm that there are fewer isolated voids inside. On the other hand, it can be confirmed that Figure 3 The void structure of the sintered body (b) is dispersed in the main body starting from the three key points of the grain boundary, and is rarely connected to each other.
[0117] The observation results of the microstructure using three-dimensional SEM do not conflict with the microstructure of the PZT high-density aggregate and PZT sintered body derived using the BET specific surface area based on the above-mentioned multi-point BET method, confirming that the above-mentioned discussion using the BET specific surface area is appropriate.
[0118] In addition, the specific surface area of the voids connected to the outer surface of the PZT high-density condensed film made at a pressing pressure of 750 MPa used in the above-mentioned three-dimensional SEM analysis can be estimated to be 11.23 μm based on the specific surface area of the raw material particles calculated from the particle size and mixing ratio of the raw material particles (73.8:26.2) and the volume density of the voids connected to the outer surface relative to the overall voids analyzed by the three-dimensional SEM image (98%). 2 / μm 3 .
[0119] Table 2
[0120]
[0121] The relationship between the volume density of voids connected to the outer surface relative to the overall voids and the overall porosity derived from the results of the multi-point BET method and three-dimensional SEM image observation is shown in FIG. Figure 4 .
[0122] Figure 4 The three white circles on the solid line above are curves of PZT agglomerates obtained by the manufacturing method of the agglomerate used in the present invention, using solidification pressures of 400MPa, 750MPa, and 1000MPa from the right, respectively. The two on the left are high-density agglomerates with a porosity of less than 20%, which is equivalent to the present invention, and the one on the right is a compressed powder with a porosity of 33.5% outside the scope of the present invention. The specific surface area of the voids connected to the outer surface of these is roughly equal to the specific surface area of the raw material powder.
[0123] Figure 4 The solid line at the bottom represents the relationship between the volume density of the voids connected to the outer surface of the PZT sintered body and the overall voids and the overall porosity. The black circle on the right represents the formed body before sintering (uncompressed), the black circle in the middle represents the sintered body with a porosity of 21.8% obtained in this embodiment, and the black circle on the left represents the sintered body with the same porosity of 4%.
[0124] As described above, in the sintered body, as the raw material particles grow in crystal form by sintering, the volume density of voids communicating with the outer surface relative to the total voids decreases as the porosity decreases.
[0125] exist Figure 4 In the figure, the central dotted line represents the relationship between the volume density of voids connected to the outer surface and the overall porosity of a compact obtained from a pressed body of alumina particles obtained by a usual one-stage compression, within the range of suppressing the breakage of the raw material particles as much as possible, regardless of the manufacturing method of the agglomerate of the present invention.
[0126] The black squares on the dotted line are drawn by drawing the alumina described in Patent Document 5 and Non-Patent Document 1 as a compact having the lowest porosity known in the past, obtained by a normal one-stage compression within the range of suppressing the crushing of the raw material particles as much as possible. Considering that the alumina is a pressed powder, it is assumed that the volume density of the voids connected to the outer surface relative to the overall voids is equal to Figure 4 The same value of the powder compact above, Figure 4 The upper solid line is drawn.
[0127] When the formed body is formed, for example, by sintering or by forming accompanied by crushing of the raw material particles, it is believed that the porosity can be further reduced, but it is believed that as a result, the volume density of the voids connected to the outer surface relative to the overall voids is also reduced as shown by the dotted line due to the crystal growth or crushing of the raw material particles.
[0128] The above curves of the PZT sintered body and alumina show that in the conventional kiln method accompanied by heat treatment and particle crushing, the voids integrated in the green compact become dispersed as the porosity decreases, thereby the maximum void density tends to decrease.
[0129] On the other hand, the high-density agglomerate of the present invention suppresses the breakage of the raw material particles as much as possible and does not produce crystal growth. Therefore, even if the porosity is less than 20%, it can maintain the same volume density of voids connected to the outer surface relative to the overall voids as that of the conventional particle forming body before sintering, which is approximately 100%.
[0130] It can be seen that the curve of the above-mentioned aluminum oxide and the curve of the sintered body of PZT can represent the limit areas of the porosity of the prior art and the volume density of the voids connected to the outer surface relative to the overall voids. On the other hand, by utilizing the high-density agglomerate of the present invention, by further sintering or compressing it, it is possible to manufacture a structure having a porosity of less than 20% and a volume density of the voids connected to the outer surface of 60% to 65% or more relative to the overall voids.
[0131] From the viewpoint of impregnation with silicone oil, a liquid in which nanoparticles are dispersed, or a liquid resin described later, the average gap width between the particles of the high-density agglomerate of the present invention is preferably 200 nm or less. Figure 4 The specific surface area of the voids communicating with the outer surface of the PZT high-density coacervate film observed in the three-dimensional SEM image shown above can be estimated to be 11.23 μm 2 / μm 3 The average void width of the void part of the PZT high-density condensed film connected to the outer surface of the PZT particles is approximately "void volume (48.38μm 3 )" divided by "half the surface area (11.23 μm 2 / μm 3 ×343μm 3 / 2)” is 25nm.
[0132] Figure 5 (a) is a SEM image of the fracture surface of a film cured by impregnating epoxy in a PZT high-density coacervate film. The PZT high-density coacervate film deposited on aluminum foil was punched out with circles of 11.24 mm and 13 mm in diameter, and a drop of low-viscosity epoxy resin 50-minute curing type 2-component type (manufactured by Shinichi Resin Co., Ltd.) was dropped on the surface of the PZT film. Two PZT high-density coacervate films were placed opposite each other and cured while applying a pressure of 400 MPa.
[0133] Figure 5(b) is a SEM image of the fracture surface of a film solidified by impregnating PMMA into a high-density condensed film of PZT. PMMA is dissolved in acetone and sprayed onto the first and second PZT particles on the SUS foil to dry and reduce them to powder. The amount of PMMA blown is equal to the amount of void volume generated when the first and second PZT particles are highly densified. After the first and second PZT particles on the SUS foil and the PMMA powder are repeatedly pressed and stacked on aluminum foil to form a high-density condensed film, acetone is dripped with a dropper to dissolve PMMA again, and it is solidified again by drying to produce the film.
[0134] <Example 2> Physical properties of high-density condensed films using PZT particles
[0135] Next, the leakage current characteristics and polarization characteristics of the high-density aggregate film of the present invention were studied.
[0136] In order to evaluate the electrical properties, an Au electrode with an area of 0.5 mm×0.5 mm and a thickness of 400 nm was deposited on the surface of each PZT by sputtering. Figure 6 The graphs respectively show the leakage current characteristics of a PZT compressed powder film with a porosity of about 35% impregnated with silicone oil, the change in leakage current characteristics before and after silicone oil impregnation of a PZT high-density condensed film with a porosity of 11% to 15%, and the leakage current characteristics of a PZT high-density condensed film with a porosity of less than about 10% impregnated with silicone oil.
[0137] In a conventional powder compact with a porosity of about 35%, even if impregnated with silicone oil, the insulation breakdown will be immediately caused by the very high leakage current. In contrast, in a PZT high-density coagulated film with a porosity of 11% to 15%, the leakage current is reduced by about 4 orders of magnitude, and by impregnating it with silicone oil, it can be confirmed that the leakage current is further reduced by about 1 order of magnitude. Moreover, a PZT high-density coagulated film with a porosity of less than about 10% impregnated with silicone oil showed a leakage current of 4.67×10 -7 A / cm 2 Very excellent insulation properties.
[0138] Figure 7 The figure shows the case where a PZT high-density coacervate film with a porosity of less than 10% is impregnated with silicone oil and the case where a PZT high-density coacervate film with a porosity of about 10% is impregnated with TiO dispersed in ethanol. 2 Graph of the respective polarization properties of a solution of nanoparticles and re-pressing at 900 MPa.
[0139] Both showed saturated polarization characteristics. In addition, in the PZT high-density condensed film impregnated with silicone oil, the residual polarization value (P r ) is 38μC / cm 2, coercive electric field (E c ) is 280 kV / cm. On the other hand, in the case of a TiO 2 The PZT nanoparticles in the solution are highly dense aggregates. r Increased to 37μC / cm 2 , coercive electric field (E c ) increased to 400 kV / cm.
[0140] This suggests that the functionality of a PZT high-density coacervate film can be controlled by impregnating it with nanoparticles, resin, etc.
[0141] <Example 3> Stacking of high-density aggregates sandwiched between electrode layers ( Figure 8 )
[0142] (1) Manufacturing of Unit 1
[0143] PZT particles (average particle size: 1550 nm) serving as first particles adhere to the surface of SUS304 (film thickness: 20 μm).
[0144] The first PZT particles were synthesized by the molten salt method using PZT-LQ powder manufactured by Sakai Chemical Industry. The first PZT particles were weighed with a microanalytical balance (SHIMADZU, model: AEM-5200), moved to a 50cc glass container filled with ethanol, and dispersed for 1 minute using an ultrasonic homogenizer (SONIC & MATERIALS, model: VCX750) with 350W, 20kHz ultrasonic waves. The solution was moved to an air brush coating system (GSI Creos, PS311 air brush kit) and sprayed on the SUS304 of the transfer plate prepared in advance on a hot plate set at 60°C, thereby attaching the first PZT particles to the SUS304 surface.
[0145] The second particles are attached to the first particles so that the mixing ratio of the second particles (volume occupied by the second particles / total volume of the first particles and the second particles) is between 15% and 30%.
[0146] The spraying of the second particles is carried out in the same manner as the first particles. The second particles use PZT particles (average particle shape: 150 nm). The second PZT particles are first made into a sintered body using PZT-LQ powder manufactured by Sakai Chemical Industry. After being made into a powder using a mortar, they are placed in a zirconia ball mill tank together with zirconia balls and acetone, and crushed using a planetary ball mill. The acetone is dried, and the obtained powder is dispersed in ethanol, placed in a centrifuge, and subjected to classification treatment to obtain the second PZT particles. The second PZT particles are also dispersed in ethanol like the first PZT particles, and then sprayed onto the surface of SUS304 to which the PZT particles are attached, thereby attaching to the first PZT particles.
[0147] The SUS304 with the first and second particles attached is removed from the hot plate and cut into multiple circular plates with a diameter of 13 mm. The first and second PZT particles attached to the SUS304 are used to clamp a substrate of a 13 mm diameter aluminum foil (film thickness 20 μm) with aluminum terminals with a width of 1 mm and a length of 5 mm. By applying curing pressure, the PZT particles are cured on both sides of the aluminum foil substrate, and the first and second particles are transferred to both sides of the substrate.
[0148] The substrate is preferably a metal or carbon having an elastic modulus of 180 GPa or less. The solidification pressure is preferably lower than the pressure of crushing the raw material particles, and the solidification pressure is 2 GPa or less.
[0149] In this experiment, the first and second particles were transferred eight times at 450 MPa to both sides of an aluminum foil, and then pressed at 900 MPa using a hard chrome-plated steel material to deposit a 20 μm thick insulating PZT layer on each side of the aluminum foil.
[0150] A highly dense aggregate film having electrical conductivity may be provided between the substrate and the highly dense aggregate film of insulating PZT.
[0151] As a comparative reference example, the first and second PZT particles were transferred using a conductive mesh foil as a substrate. The conductive mesh foil was produced by sputtering gold electrodes on both sides of PET in which holes with a diameter of 250 μm were formed at a pitch of 300 μm by laser processing.
[0152] exist Fig. 9 A microscopic photograph of the obtained condensed film is shown in FIG. Fig. 9 As shown, the first and second PZT particles cannot be fully transferred to the hole portion and the periphery of the hole of the substrate (scattered in the dark portion 14), and the first and second PZT particles cannot be solidified. It should be noted that 13 is a reference for the portion where the condensed film is not formed to become a dark portion, and the condensed film portion formed by transfer is wiped off.
[0153] Next, a 1 cm thick layer of PZT was sputtered on both sides of the surface. 2 φ of gold, thereby depositing an electrode layer.
[0154] The deposition of the electrode layer is preferably carried out by a deposition method that does not block the pores of the high-density agglomerates because PMMA is impregnated into the high-density agglomerate film of PZT in the next step. It can be sputtering or vacuum evaporation, and can also form a high-density agglomerate film with conductivity.
[0155] Both surfaces of the high-density PZT coagulation film with gold sputtered were impregnated with PMMA dissolved in PEGMEA, and a 1 cm conductive electrode with a terminal of 1 mm in width and 5 mm in length was used. 2 The φ grid-shaped foil is clamped at 6N / cm on one side. 2 While being restrained, PEGMEA was volatilized at 60°C and PMMA was cured.
[0156] In this experiment, a conductive mesh foil was produced by sputtering gold electrodes on both sides of PET having holes of 250 μmφ in diameter opened at a pitch of 300 μm by laser processing, but a foil having similar fine holes opened in a metal foil is also preferred, a cloth woven with conductive threads of metal, carbon, etc. is also preferred, and a conductive mesh foil produced by a 3D printer is also preferred.
[0157] The relative dielectric constant of the cell 1 obtained in this way was 136.
[0158] As a comparative reference example, PMMA dissolved in PEGMEA was used to directly bond a conductive mesh foil without an electrode layer to the high-density coacervate films on both sides of the substrate in the same manner as above. The relative dielectric constant of the obtained cell was 0.67.
[0159] From this, it is considered that sufficient adhesion as an electrode cannot be obtained with the high-density PZT aggregate film only using the conductive mesh-shaped foil.
[0160] As a comparative reference example, a conductive mesh foil and a high-density coacervate film of PZT were directly brought into contact without using PMMA dissolved in PEGMEA, and a curing pressure of 1 GPa was applied to attempt bonding. However, Fig.10 As shown, it is not possible to engage ( Fig.10 The left and right sides are grid-shaped foils, and the center is a substrate with high-density condensation films on both sides).
[0161] (2) Manufacturing of Unit 2
[0162] Three units of the unit 1 manufactured in (1) were stacked (unit 2). PMMA dissolved in PEGMEA was impregnated between the units 1 while the pressure was 6 N / cm 2 While being restrained, PEGMEA was volatilized at 60° C., thereby solidifying PMMA.
[0163] Thus, when the unit 1 is stacked, it is not necessary to press the unit 1 with a clamping jig or the like, and an integrated electric component unit can be manufactured.
[0164] <Example 4> Removal of the solidified resin on the surface of the high-density coacervate film
[0165] It is very difficult to impregnate and cure a press-formed high-density coacervate film with a resin that is neither too much nor too little, and to expose only the surface of the high-density coacervate film. For example, when a liquid containing a resin such as PMMA dissolved in a solvent is impregnated and then the solvent is volatilized to cure, there is a problem that the cured resin does not reach the surface of the high-density coacervate film due to the reduction in volume caused by the volatilization of the solvent, or that too much liquid is applied and the remaining resin is cured to form a surface layer. In addition, in the case of impregnation with epoxy resin, if the remaining part before curing that overflows to the surface is removed with silicone rubber, there is a problem that the press-formed high-density coacervate film alone is easily destroyed.
[0166] For example, if an upper electrode is formed by sputtering or the like on a high-density coagulation film exhibiting strong dielectric properties, and the remaining resin is solidified to form a surface layer, the electric field is concentrated on the solidified remaining resin between the upper electrode and the high-density coagulation film exhibiting strong dielectric properties, and there is a problem that the strong dielectric properties and piezoelectric properties are not exhibited. In addition, when the upper electrode is pre-deposited on the high-density coagulation film and then impregnated with resin, and the remaining resin is solidified to form a surface layer, there is a problem that the solidified remaining resin on the surface layer hinders the connection between the upper electrode and the circuit.
[0167] The inventors of the present invention have found that the dissolution rate into an organic solvent and the swelling rate when immersed in an organic solvent are different between the resin that is impregnated into the interior of the high-density cohesive film and the resin that is solidified on the surface and forms a surface layer, and have found that this manufacturing method can solve the above-mentioned problems. Next, a specific manufacturing method will be described using PZT as an example.
[0168] PZT particles (average particle size: 1550 nm) serving as first particles adhere to the surface of stainless steel SUS304 (film thickness: 20 μm).
[0169] The first PZT particles were synthesized by the molten salt method using PZT-LQ powder made by Sakai Chemical Industry. The first PZT particles were weighed using a microanalytical balance (SHIMADZU, model: AEM-5200), moved to a 50cc glass container filled with ethanol, and dispersed for 1 minute using an ultrasonic homogenizer (SONIC & MATERIALS, model: VCX750) with 350W, 20kHz ultrasound. The solution was moved to an air brush coating system (GSI Creos, PS311 air brush kit) and sprayed on the SUS304 of the transfer plate prepared in advance on a hot plate set at 60°C, thereby attaching the first PZT particles to the SUS304 surface.
[0170] Next, the second particles are attached to the first particles so that the mixing ratio of the second particles (volume occupied by the second particles / total volume of the first particles and the second particles) is between 15% and 30%.
[0171] The spraying of the second particles is the same as that of the first particles. The second particles use PZT particles (average particle shape: 150nm). The second PZT particles are first made into a sintered body using PZT-LQ powder produced by Sakai Chemical Industry. After being made into powder using a mortar, they are placed in a zirconia ball mill tank together with zirconia balls and acetone, and crushed using a planetary ball mill. The acetone is dried, and the obtained powder is dispersed in ethanol, placed in a centrifuge, and subjected to classification treatment to obtain the second PZT particles. The second PZT particles are also dispersed in ethanol like the first PZT and then sprayed onto the surface of SUS304 with PZT particles attached, thereby attaching to the first PZT particles.
[0172] The SUS304 with the first and second particles attached is removed from the hot plate and cut into multiple pieces of 1 cm 2 The first and second particles were pressed on a substrate of aluminum foil (film thickness 20 μm) in the shape of a disk of φ, and pressure-transferred and cured on the substrate.
[0173] The substrate is preferably a metal or carbon with an elastic modulus of 180 GPa or less. It is preferably characterized by a solidification pressure lower than the pressure of crushing the raw material particles, which is 2 GPa or less. In this experiment, the pressure was 1000 MPa. The first and second particles were pressurized and transferred from SUS304 to the aluminum foil substrate, and this operation was repeated 9 times, thereby laminating a high-density cohesive film of PZT on the aluminum foil. Fig.11 (a) is a schematic diagram of a sample in which an Au upper electrode is sputtered on the surface of the PZT high-density condensed film. The area of the Au upper electrode is 0.5 mm×0.5 mm, and the thickness is 400 nm.
[0174] Next, if Fig.11 As shown in (b), epoxy resin is impregnated so as to cover the surface. A low-viscosity epoxy resin 50-minute curing type 2-component type (manufactured by Shinichi Plastics Co., Ltd.) is used. After the impregnation treatment, the epoxy resin is crosslinked and cured by heat treatment at 70°C for more than 2 hours.
[0175] Next, if Fig.11 As shown in (c), cyclohexane was applied to a few mL of the sample surface and allowed to stand for 30 minutes to allow only the remaining epoxy resin on the surface layer to swell. Fig.11 As shown in (d), carefully peel it off with tweezers. Fig.11 As shown in (e), the high-density condensed film of PZT and the Au upper electrode are exposed.
[0176] Fig.12 (a) is Fig.11 The surface SEM image of the Au upper electrode shown in (e) is shown in FIG. Fig.12 (b) indicates Fig.11 (b) shows a surface SEM image before the residual epoxy resin is peeled off. In the comparative reference example, the PZT particles could not be confirmed by SEM due to the residual epoxy resin in the surface layer, but by peeling off the swelling treatment with the cyclohexane mentioned above, it was possible to confirm that the PZT high-density condensed film impregnated with epoxy resin and the Au upper electrode were exposed.
[0177] It is believed that the excess epoxy resin in the cured surface layer is in "surface" contact with cyclohexane, but the cyclohexane that reaches the epoxy resin impregnated in the high-density cohesive film of PZT is in "point" contact and is therefore difficult to swell, resulting in that only the excess epoxy resin in the surface layer can be removed.
[0178] Fig.13 (a) is the polarization characteristic of the high-density condensed film of PZT impregnated with epoxy resin. A fully saturated hysteresis loop can be confirmed. Fig.13 In the comparative reference example shown in (b) where excess epoxy resin remained on the surface layer, the excess epoxy resin hindered the circuit connection between the Au upper electrode and the ferroelectric evaluation device, and the hysteresis loop could not be displayed.
[0179] In addition, even if Kapton adhesive tape is pasted on the surface of the PZT high-density condensed film impregnated with epoxy resin and then peeled off, the PZT high-density condensed film will not peel off from the aluminum foil of the substrate, but the PZT high-density condensed film impregnated with silicone oil is easily peeled off from the aluminum foil of the substrate.
[0180] This makes it possible to produce a highly dense cohesive film having high bonding strength and ceramic functionality.
[0181] <Example 5> Fabrication of a flexible sheet-shaped all-solid-state lithium-ion battery
[0182] All-solid-state lithium-ion batteries using polymer solid electrolytes have lower ion conductivity than liquid electrolytes, and there is a problem that they cannot be charged or discharged unless the temperature reaches 50°C or above. In addition, polymer electrolytes have problems such as high viscosity and time required for impregnation, and there are also problems in achieving high energy density by containing active materials at high density. It was found that the high-density agglomerate of the present invention has the characteristic of allowing liquid to be impregnated in every corner. By using this structure to impregnate the polymer solid electrolyte into the electrode layer, the diffusion movement distance of lithium ions can be greatly shortened, and an all-solid-state lithium-ion battery that can also operate at room temperature can be made.
[0183] The all-solid-state lithium-ion battery preferably has a positive electrode sheet having a high-density coagulation film of a positive electrode active material formed on a substrate and a negative electrode sheet having a coagulation film of a negative electrode active material formed on a substrate, and preferably has the feature that these positive electrode sheets and negative electrode sheets are impregnated with a polymer electrolyte. The polymer electrolyte may also be an uncrosslinked polymer electrolyte, but is preferably a crosslinked and solidified polymer solid electrolyte. In addition, it is preferred to have a polymer electrolyte layer between the high-density coagulation film of the positive electrode active material and the coagulation film of the negative electrode active material.
[0184] The thickness of the high-density agglomerate of the positive electrode sheet and the thickness of the agglomerate film of the negative electrode sheet are preferably about 3 μm to 50 μm, and can be between 1 μm and 300 μm. In addition, the porosity of the high-density agglomerate of the positive electrode sheet is preferably less than 20%, and the porosity of the agglomerate of the negative electrode sheet can be less than 35%.
[0185] The positive electrode active material is not limited to the following, and examples thereof include lithium cobalt oxide (LCO), lithium manganese oxide, lithium nickel oxide, nickel cobalt manganese oxide, nickel cobalt aluminum oxide, and lithium iron phosphate.
[0186] The negative electrode active material is not limited to the following, and examples thereof include lithium titanate (LTO), carbon, and metal silicon.
[0187] The substrate of the positive electrode is preferably aluminum, but is preferably coated with corrosion-resistant Au, Pt, metal with an elastic modulus below 180 GPa or carbon. The thickness of the substrate of the positive electrode is preferably between 10 μm and 30 μm, and may also be between 5 μm and 50 μm.
[0188] The substrate of the negative electrode sheet is preferably aluminum coated with Au at a thickness of 10 nm to 1 μm, but may also be aluminum coated with Li + The metal or carbon having elastic modulus of Cu and Pt having resistance is 180 GPa or less. The thickness of the substrate of the negative electrode sheet is preferably between 10 μm and 30 μm, but may also be between 5 μm and 50 μm.
[0189] The polymer electrolyte layer may be an uncrosslinked polymer electrolyte, but preferably a crosslinked and solidified polymer solid electrolyte. In addition, the higher the ion conductivity of the polymer electrolyte layer, the better, but as long as it has 1×10 -6 The thickness of the polymer electrolyte layer is preferably 1 μm to 20 μm, but may be between 100 nm and 50 μm.
[0190] Next, an example of a specific production method will be described.
[0191] LiCoO is used as the positive electrode active material 2(LCO) powder. The powder is commercially available ("Cellseed 5hV" manufactured by Nippon Chemical Industry Co., Ltd.). 0.5 g of LCO and 50 mL of ethanol / silicon nitride balls (10 mmφ, 5 mmφ, 2 mmφ, about 500 g in total) were placed in a 500 cc zirconia container (manufactured by Fritsch), and pulverized at 200 rpm for 12 hours using a planetary ball mill (manufactured by Fritsch, P-6 standard line).
[0192] Ethanol was added to make the liquid taken out from the planetary ball mill reach 250 mL, and centrifugal separation was performed at a centrifugal force of 470×g for 5 minutes. Fig.14 (a) shows an SEM image of the precipitated particles. The average particle size is about 1 μm. The particles are referred to as the first LCO particles. The solution remaining in the centrifugal separation is evaporated to about 70 mL in a vacuum dryer. The obtained liquid is referred to as the second LCO solution, and the particles obtained by drying the second LCO solution are referred to as the second LCO particles. Fig.14 The SEM image of the second LCO particles is shown in (b). It can be confirmed that the second LCO particles are more fully crushed than the first LCO particles. If the second LCO particles are observed by SEM at a higher magnification, Fig.14 As shown in (c), it was confirmed that nanosheets with a thickness of several nm and a width of several nm to about 1 μm were contained.
[0193] Next, an alumina-coated SUS304 was prepared in which an alumina film with a thickness of about 1 μm was deposited on a stainless steel SUS304 foil (film thickness 20 μm) by the AD method. LCO particles, which became the first particles, were attached to the surface of the alumina film. The first LCO particles were weighed using a microanalytical balance (SHIMADZU, model: AEM-5200), transferred to a 50 cc glass container filled with super dehydrated heptane, and dispersed for 1 minute using an ultrasonic homogenizer (SONIC & MATERIALS, model: VCX750) with 150 W, 20 kHz ultrasonic waves. The solution was transferred to an air brush coating system (GSI Creos, PS311 air brush kit), and sprayed onto the alumina-coated SUS304 on a transfer plate prepared in advance on a hot plate set at 70°C, so that the first LCO particles were attached to the surface of the alumina-coated SUS304.
[0194] Next, the second LCO particles are attached to the first LCO particles in such a manner that the mixing ratio of the second LCO particles (volume occupied by the second particles / total volume of the first particles and the second particles) is between 15% and 35%. The second LCO particles are sprayed with a second LCO solution. Similar to the first LCO particles, the second LCO particles are attached to the first LCO particles by spraying the surface of the alumina-coated SUS304 to which the first LCO particles are attached.
[0195] The alumina-coated SUS304 to which the first and second LCO particles were attached was removed from the hot plate and subjected to a heat treatment at 350° C. for 5 minutes in air having a dew point temperature of −40° C. or less.
[0196] Next, prepare a square aluminum foil substrate (area 6mm×10mm, film thickness 12μm). In order to easily visually identify that it is a positive electrode sheet, an Au film with a thickness of 400nm is sputtered on the surface of the square aluminum foil opposite to the surface where the LCO is solidified. In air with a dew point temperature below -40°C, the first and second LCO particles are pressed on the surface of the aluminum, pressurized and transferred, and solidified on the substrate. It is preferred that the solidification pressure is lower than the pressure of the crushed raw material particles, and is less than 2GPa. In this experiment, 420MPa was pressurized. The first and second particles are pressurized and transferred from the alumina-coated SUS304 to the aluminum foil substrate, and the operation is repeated 4 times, thereby stacking a high-density condensed film of LCO on the aluminum foil. The thickness of the LCO high-density condensed film is about 5μm. A positive electrode sheet is obtained by these methods.
[0197] Li is used as the negative electrode active material 4 Ti 5 O 12 Powder of LTO. The powder used was a commercially available powder (LTO-2, manufactured by Xiamen Tmax Battery Equipments Limited) in which the surface of LTO particles was coated with carbon, and a powder synthesized from a reagent.
[0198] First, prepare a solution in which 1 g of commercially available carbon-coated LTO particles are dispersed in 250 mL of ethanol, centrifuge at 75×g, remove the liquid and fully dry it to obtain a powder. The particles of this powder are referred to as the first LTO particles. Fig.15 (a) shows a SEM image of the particles. The average particle size is about 800 nm.
[0199] Next, lithium carbonate (made by high-purity chemical, LIH06XB) and titanium dioxide (made by high-purity chemical, TIO14PB) were weighed so that Li 4 Ti 5 O 12The fixed ratio composition becomes 20g, and together with 200mL of ethanol and silicon nitride balls (10mmφ, 5mmφ, 2mmφ, about 500g in total), it is placed in a 500cc zirconia container (made by Fritsch), and the mixture is crushed and mixed at 500rpm for 2 hours using a planetary ball mill (made by Fritsch, P-6 standard line). The obtained liquid is transferred to a tray, and after being fully dried at 80°C, the obtained mixed powder is transferred to an alumina crucible and heat-treated at 800°C for 6 hours. The obtained powder was again placed in a 500cc zirconia container (manufactured by Fritsch) together with 200mL of ethanol and silicon nitride balls (10mmφ, 5mmφ, and 2mmφ, totaling about 500g), and pulverized at 500rpm for 2 hours using a planetary ball mill (manufactured by Fritsch, P-6 standard line). The powder was transferred to a tray, and after being fully dried at 80°C, the obtained powder was transferred to an alumina crucible and heat treated at 800°C for 6 hours to obtain LTO powder.
[0200] 1 g of the LTO powder, 50 mL of ethanol, and silicon nitride balls (10 mmφ, 5 mmφ, and 2 mmφ, totaling about 500 g) are placed in a 500 cc zirconia container (manufactured by Fritsch), and pulverized at 250 rpm for 18 hours using a planetary ball mill (manufactured by Fritsch, P-6 standard line). After adding ethanol until the resulting liquid becomes 500 mL, centrifuge at a centrifugal force of 836×g for 15 minutes, and evaporate the ethanol in a vacuum dryer until the liquid after centrifugation becomes 100 mL. The concentrated liquid is set as the second LTO solution. In addition, half (50 mL) of the second LTO solution is transferred to another container, and further dried in a vacuum dryer to obtain LTO powder. The particles of the LTO powder are set as the second LTO particles. Fig.15 The SEM image of the second LTO particle is shown in (b). It can be confirmed that the second LTO particle is more fully crushed than the first LTO particle. If the second LTO particle is observed by SEM at a higher magnification, Fig.15 As shown in (c), it was confirmed that nanosheets with a thickness of several nm and a width of several nm to about 1 μm were contained.
[0201] Next, an alumina-coated SUS304 with an alumina film of about 1 μm thickness deposited on a stainless steel SUS304 foil (film thickness 20 μm) by the AD method was prepared. LTO particles, which became the first particles, were attached to the surface of the alumina film. The first LTO particles were weighed using a micro-analytical balance (SHIMADZU, model: AEM-5200), transferred to a 50cc glass container filled with ethanol, and dispersed for 1 minute using an ultrasonic homogenizer (SONIC & MATERIALS, model: VCX750) with 150W, 20kHz ultrasound. The solution was transferred to an air brush coating system (GSI Creos, PS311 air brush kit), and the first LTO particles were attached to the surface of the alumina-coated SUS304 by spraying the alumina-coated SUS304 on a transfer plate prepared in advance on a hot plate set at 70°C.
[0202] Next, the second LTO particles and the first LTO particles were weighed using a microanalytical balance (SHIMADZU, model: AEM-5200) so that the mixing ratio of the second LTO particles (volume occupied by the second particles / total volume of the first and second particles) was about 25%, and transferred to a 50cc glass container filled with ethanol, and a solution was prepared by using an ultrasonic homogenizer (SONIC & MATERIALS, model: VCX750) with 150W, 20kHz ultrasonic waves for 1 minute. The solution containing the first and second LTO particles was sprayed on the surface of the alumina-coated SUS304 to which the first LTO particles were attached, similarly to the first LTO particles, so that the mixture of the first and second LTO particles was attached to the first LTO particles.
[0203] Next, the second LTO particles are attached to the first and second mixed LTO particles so that the mixing ratio of the first LTO particles and the second LTO particles attached initially by spraying is between 15% and 35%. The second LTO solution is used for spraying the second LTO particles.
[0204] The alumina-coated SUS304 with the first and second LTO particles attached thereto was removed from the hot plate and subjected to a heat treatment at 350° C. for 5 minutes in an atmosphere having a dew point temperature of −75° C. or less and an oxygen concentration of 50 ppm or less.
[0205] A square aluminum foil (area 8mm×12mm, film thickness 13μm) substrate with Au sputtered on the surface with a thickness of about 400nm was prepared, and the first and second LTO particles were pressed on the Au sputtered surface in air with a dew point temperature below -40°C, and pressurized and transferred to solidify on the substrate. The Au sputtered film is used to prevent aluminum from being bonded to Li + The barrier layer can also be a barrier to Li+ Cu, Pt, etc. with high resistance. Preferably, the solidification pressure is lower than the pressure of crushing the raw material particles, and is less than 2GPa. In this experiment, the pressure was applied at 420MPa. The first and second particles were pressurized and transferred from the alumina-coated SUS304 to the aluminum foil substrate, and this operation was repeated 4 times to laminate the LTO coagulation film on the aluminum foil. The thickness of the LTO coagulation film is about 5μm. By this method, a negative electrode sheet is obtained.
[0206] The present invention describes a method for making an all-solid-state lithium-ion battery by impregnating a positive electrode sheet and a negative electrode sheet with a polymer solid electrolyte and joining the positive electrode sheet and the negative electrode sheet using the polymer solid electrolyte. The commercially available "all-solid-state polymer electrolyte" (20 wt% of the polymer electrolyte and the crosslinking initiator are dissolved in acetonitrile) made by Osaka Soda Co., Ltd. is used as the polymer solid electrolyte. The ion conductivity of the all-solid-state polymer electrolyte synthesized in this experiment is 2×10 -5 S / cm.
[0207] Fig.16 (a) is the negative electrode. In air with a dew point temperature below -40°C, the polymer electrolyte dissolved in acetonitrile and the crosslinking initiator are fully mixed in a specified amount, such as Fig.16 As shown in (b), the solution is impregnated into the negative electrode sheet. Then, the acetonitrile is fully volatilized to prepare Fig.16 The negative electrode sheet impregnated with the polymer electrolyte and the crosslinking initiator is shown in (c). The positive electrode sheet is also impregnated in the same manner, and the acetonitrile is fully volatilized to prepare a positive electrode sheet impregnated with the polymer electrolyte and the crosslinking initiator. Fig.16 The polymer electrolyte was cross-linked by bonding the polymer electrolyte to the substrate in a manner that prevents air from entering the substrate as shown in (d) of FIG. 1 , and heat-treating the polymer electrolyte at a dew point temperature of -70°C or less and an oxygen concentration of 50 ppm or less at 70°C for 1 hour to produce the polymer electrolyte. Fig.16 The all-solid-state lithium-ion battery shown in (e) has a polymer electrolyte layer provided between the positive electrode sheet and the negative electrode sheet having a thickness of about 20 μm.
[0208] As a comparative reference example, we also made Fig.16 (f) shows a commercially available all-solid polymer electrolyte sheet (ion conductivity: 5×10 -5 S / cm) of all-solid-state lithium-ion battery.
[0209] exist Fig.17The charge and discharge curve of the prepared all-solid-state lithium-ion battery is shown in the figure. The evaluation conditions are 25°C and 0.01C. The characteristics of the charge and discharge curve of a typical LCO are obtained from the all-solid-state lithium-ion battery in which a polymer solid electrolyte is impregnated in a high-density coacervate film, and it is confirmed that charging and discharging can be performed at room temperature. On the other hand, the battery prepared by separating the all-solid-state polymer electrolyte sheet cannot be fully charged and discharged.
[0210] Thus, by impregnating every corner of the high-density coacervate film with a polymer solid electrolyte, it is possible to operate an oxide-based all-solid-state lithium-ion battery that can operate even at room temperature.
[0211] <Example 6> All-solid-state lithium-ion battery with flexibility and bending
[0212] In the past, whether it was a liquid or solid-state lithium-ion battery, the battery cells were wound and stored in a shell like a "prismatic lithium-ion battery", or the battery cells were stacked and the terminals were taken out from the edge for bonding, like a "laminated lithium-ion battery", to achieve high capacity. However, there are issues such as the shape of the shell taken out from the edge, the terminals of the positive and negative electrodes, etc., which restrict the shape of the entire battery.
[0213] The inventors have found that by using a high-density coacervate membrane as an electrode layer, impregnating the structure with a polymer solid electrolyte, and then embedding ceramic particles in the polymer electrolyte layer, a flexible and bendable battery cell can be produced. Fig.18 The folded battery shape shown in (a) Fig.18 Batteries with high shape freedom, such as the battery shape in which the ends of the battery sheets are bent and stacked as shown in (b). Moreover, if the battery structure is bent and stacked, the positive and negative terminals can be directly taken out not only from the edge but also from the surface. In addition, a solid battery in which a cloth containing resin such as CFRP or FRP and the bent battery sheets are stacked and the whole is covered with a cross-linked resin can become a structural member such as the housing of a smartphone.
[0214] like Fig.19 As shown in (a), the flexible and bendable battery sheet preferably has a polymer solid electrolyte layer embedded with ceramic particles between the above-mentioned positive electrode sheet impregnated with a polymer solid electrolyte and the negative electrode sheet. The ceramic particles may also be non-contacting Li during charge and discharge. + Reactive substances, such as SiC, SiO 2 、Si 3 N 4 and oxides such as aluminum oxide and zirconium oxide. In addition, it can also be a lithium ion conductor with a lower reduction potential than the negative electrode active material, such as Li 2+, a garnet-type lithium ion conductor. 7 La3 Zr 2 O 12 The particle shape of the ceramic particles is preferably between 100nm and 10μm. The thickness of the polymer solid electrolyte layer in which the ceramic particles are embedded is preferably about 1μm to 10μm, and can be between 100nm and 50μm. The content of the ceramic particles in the polymer solid electrolyte layer is preferably between 10% and 70% in the case of oxides that do not show lithium ion conductivity, and between 10% and 80% in the case of lithium ion conductors, and can also be a high-density agglomerate.
[0215] Next, an example of a specific method for manufacturing a bendable and flexible all-solid-state lithium-ion battery will be described.
[0216] Alumina particles (Sumicorundum AA-2 manufactured by Sumitomo Chemical, average particle size: 2 μm) were attached to the surface of stainless steel SUS304 (film thickness: 20 μm).
[0217] The AA-2 particles were weighed using a microanalytical balance (SHIMADZU, model: AEM-5200), transferred to a 50 cc glass container filled with ethanol, and dispersed using an ultrasonic homogenizer (SONIC & MATERIALS, model: VCX750) with 150 W, 20 kHz ultrasound for 1 minute. The solution was transferred to an air brush coating system (GSI Creos, PS311 air brush kit) and sprayed onto the SUS304 of a transfer plate prepared in advance on a hot plate set at 60° C., thereby attaching the AA-2 particles to the SUS304 surface.
[0218] The SUS304 with AA-2 attached is removed from the hot plate, and after heat treatment at 350°C for 5 minutes in an environment with a dew point temperature below -40°C, the AA-2 particles are pressed onto the positive electrode sheet and the negative electrode sheet for pressurization and transfer. The preparation of the positive electrode sheet and the negative electrode sheet is the same as in Example 5. It is preferred that the pressurization and transfer pressure is lower than the pressure of the crushed raw material particles and is less than 2GPa. In this experiment, pressurization is performed at 420MPa. The AA-2 particles are pressurized and transferred from the SUS304 to the positive electrode sheet and the negative electrode sheet, and this operation is performed once.
[0219] Next, similarly to Example 5, the positive electrode sheet and the negative electrode sheet with AA-2 attached were impregnated with 20 wt% of all-solid polymer electrolyte manufactured by Osaka Soda Co., Ltd., and after the acetonitrile was fully volatilized, the high-density coacervate film of the positive electrode and the coacervate film of the negative electrode were laminated in a manner that did not enter the air, and then a pressing pressure of 7 kN was applied to squeeze out the remaining polymer electrolyte before crosslinking to produce a battery sheet. The thickness of the polymer electrolyte layer was about 5 μm, which could be made thinner than that of Example 5.
[0220] In a battery cell having a polymer electrolyte layer without ceramic particles as in Example 5, when an excessive amount of polymer electrolyte is squeezed out by pressing, a high-density coacervate film of the positive electrode active material and a coacervate film of the negative electrode come into contact and short-circuit.
[0221] After the end of the obtained battery cell is bent 180 degrees, it is heat treated at 70 degrees Celsius for 1 hour at a dew point temperature below -70 degrees Celsius and an oxygen concentration below 50 ppm to crosslink the polymer electrolyte and achieve full solidification. Fig.19 (b) and (c) show photos of a bent all-solid-state lithium-ion battery cell. In addition, after charging the bent all-solid-state lithium-ion battery cell, as shown in FIG. Fig.18 The stacking was performed as shown in (b), and a photograph confirming that the light was emitted by connecting to an LED was shown in Fig.19 (d).
[0222] exist Fig. 20 The charge and discharge characteristics of the bent all-solid-state lithium-ion battery sheet are shown in FIG. The evaluation was performed at 0.01C and 25°C. The characteristics of the charge and discharge curve unique to LCO were confirmed. As a comparative reference example, after bending in the same manner as the battery of Example 5, the polymer solid electrolyte was cross-linked and fully solidified, but the positive and negative electrodes were short-circuited and could not be charged. In addition, even if the battery of Example 5 was bent, the positive and negative electrodes were short-circuited and could not be charged.
[0223] For reference, the impedance characteristics of a 9 μm thick polymer solid electrolyte placed between 13 μm thick aluminum foils before and after bending are compared. Fig.21 . Although the polymer electrolyte layer is thinner than that of Example 5, no change was confirmed before and after bending, and no short circuit occurred. The reason why the battery of Example 5 was short-circuited when it was bent is believed to be that by bending the battery, the ceramic particles of the high-density coacervate film of the positive electrode or the coacervate film of the negative electrode flow, exerting a strong shear force on the polymer solid electrolyte, and the polymer solid electrolyte was cut. Therefore, it is believed that the ceramic particles possessed by the polymer electrolyte layer have the effect of inhibiting the flow of the positive and negative electrode active materials that work when the battery is bent.
[0224] Thus, an all-solid-state lithium-ion battery having a flexible, bent shape can be produced.
[0225] Reference numerals
[0226] 1: first particle, 2: first void, 3: second particle, 4: second void, 5: void at grain boundary 3, 6: sintered body particle, 7: unit 1, 8: unit 2, 9: substrate, 10: high-density condensed film, 11: electrode layer, 12: conductive mesh foil, 13: part of the first and second PZT particles remaining on the conductive mesh foil removed with waste cloth, 14: the first and second PZT particles remaining on the conductive mesh foil (scattered bright part), 15: Au sputtered upper electrode, 16: PZT ceramic particles, 17: aluminum substrate, 18: cross-linked epoxy resin, 19: epoxy resin swollen by cyclohexane, 20: negative electrode active material, 21: substrate of negative electrode sheet, 22: polymer electrolyte and cross-linking initiator before cross-linking dissolved in solvent, 23: polymer electrolyte and cross-linking initiator before cross-linking by volatilizing solvent, 24: substrate of positive electrode sheet, 25: positive electrode active material, 26: polymer electrolyte cured by cross-linking, 27: conductor, 28: ceramic particles.
Claims
1. A high-density agglomerate, characterized in that: It is a high-density agglomerate of oxide brittle material particles, and there are interfaces between particles and non-bonded voids between the brittle material particles constituting the high-density agglomerate, the volume ratio of the voids to the whole of the high-density agglomerate, i.e., the void ratio, is less than 20%, and the volume of the voids connected to the apparent outer surface of the high-density agglomerate relative to the overall void volume of the high-density agglomerate is more than 65%; The brittle material particles constituting the high-density agglomerate include first brittle particles and second brittle particles smaller than the first brittle particles, the second brittle particles are provided in gaps between the mutually bonded first brittle particles, and there are bonded interfaces between particles and non-bonded gaps between the plurality of second brittle particles in the gaps and between the second brittle particles and the surrounding first brittle particles; The high-density agglomerate is not sintered.
2. The high-density agglomerate according to claim 1, characterized in that: The particle size of the second brittle fine particles is 1 μm or less.
3. The high-density agglomerate according to claim 1, characterized in that: The average gap width between the brittle material particles is less than 200 nm.
4. The high-density agglomerate according to any one of claims 1 to 3, wherein Liquid or liquid resin containing nanoparticles having a particle size of 100 nm or less is dispersed in the gaps of the high-density agglomerates.
5. The high-density agglomerate according to claim 4, wherein: The liquid resin impregnated into the high-density aggregate is cured.
6. An electrical component unit, characterized in that: The invention comprises a film composed of the high-density aggregate according to any one of claims 1 to 3, an electrode layer, and a conductive mesh foil laminated in this order on both surfaces of a substrate, wherein the high-density aggregate is impregnated with a resin.
7. An electric component unit, which is formed by stacking a plurality of the electric component units according to claim 6.
8. A solid battery, characterized in that: The invention comprises a first polymer impregnated with the high-density aggregate according to any one of claims 1 to 3, wherein the first polymer has ion conductivity.
9. The solid battery according to claim 8, wherein: The solid battery has: the first polymer; and a second polymer formed on top of the first polymer, The second polymer has ion conductivity, The second polymer contains particles of brittle material.
10. The solid battery according to claim 9, wherein: The solid battery is in a bent shape.
11. The solid battery according to claim 9, wherein: The solid battery is in a bent and stacked shape.
Citation Information
Patent Citations
Brittle material structure and method for forming the same
JP2006043993A
Method for arranging nanocrystal, method for preparing nanocrystal film, substrate covered with nanocrystal film and method for producing the same
JP2012188335A
High dielectric nanosheet laminate, high dielectric element, and method for manufacturing high dielectric thin film element
JP2012240884A
Method of manufacturing lithium solid battery
JP2016100069A
Axial air gap type rotary electric machine
JP2018110527A